Win or Learn Fast Proximal Policy Optimisation - Ratcliffe, Dino; Hofmann, Katja; Devlin, Sam (IEEE Conference on Games, 2019)
AI agents within video games are often required to compete within an environment shared by many other agents. This problem can be tackled by multi-agent reinforcement learning (MARL). One solution to MARL is to learn a Nash Equilibrium Strategy (NES) that guarantees a known minimum payoff when playing against other rational agents. We focus on one approach for learning a NES, Win or Learn Fast (WoLF), WoLF has been shown to converge towards a NES in a variety of matrix-games and grid based games. Research into Deep MARL has focused on performance against opponent agents and with limited quantitative results regarding learning a NES. We present a systematic empirical investigation into the ability of Proximal Policy Optimisation (PPO) to learn a NES, showing instability in certain matrix games. We then present an extension, WoLF-PPO, that is able to learn a policy that is closer to the NES.